2017
DOI: 10.11604/pamj.supp.2017.27.3.11869
|View full text |Cite
|
Sign up to set email alerts
|

Non-protective immunity against tetanus in primiparous women and newborns at birth in rural and urban settings in Ibadan, Nigeria

Abstract: IntroductionNigeria remains among the few countries that are yet to achieve eradication of neonatal tetanus in the world despite the availability of an effective vaccine. This study investigated immunity against tetanus in primiparous mothers and neonates at birth, and identified associated factors.MethodsThis cross-sectional study involved consecutive selection of 244 primiparous mother-neonate pairs (119 from rural areas, 125 from urban areas, 137 male neonates and 107 female neonates) delivered at primary h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
8
2
Order By: Relevance
“…A secondary analysis of the 2005-06 India DHS found rural women were 48% less likely to receive antenatal TTCV than urban women (p < 0.001), although a woman was considered protected if she received even one TTCV dose [19]. A cross-sectional study of Nigerian women found those in rural areas had 2.5 greater odds of insufficient TTCV compared to urban women (p < 0.001) [20]. A multivariate analysis from Turkey found rural women actually had nearly four times greater odds of receiving at least one dose of antenatal TTCV compared to urban women (p < 0.001) [21], The researchers concluded that urban ANC providers administered less antenatal TTCV than rural ANC providers, as they felt their patients were at minimal risk for tetanus infection due to likely delivering in a hospital [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A secondary analysis of the 2005-06 India DHS found rural women were 48% less likely to receive antenatal TTCV than urban women (p < 0.001), although a woman was considered protected if she received even one TTCV dose [19]. A cross-sectional study of Nigerian women found those in rural areas had 2.5 greater odds of insufficient TTCV compared to urban women (p < 0.001) [20]. A multivariate analysis from Turkey found rural women actually had nearly four times greater odds of receiving at least one dose of antenatal TTCV compared to urban women (p < 0.001) [21], The researchers concluded that urban ANC providers administered less antenatal TTCV than rural ANC providers, as they felt their patients were at minimal risk for tetanus infection due to likely delivering in a hospital [21].…”
Section: Discussionmentioning
confidence: 99%
“…A secondary analysis of the 2005–06 India DHS found rural women were 48% less likely to receive antenatal TTCV than urban women ( p < 0.001), although a woman was considered protected if she received even one TTCV dose [ 19 ]. A cross-sectional study of Nigerian women found those in rural areas had 2.5 greater odds of insufficient TTCV compared to urban women ( p < 0.001) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Those women who reside in urban areas were 3.63 times more likely to have TT protective dose immunization as compared to their counterparts (AOR = 3.626, 95%CI: 1.510-8.707). Women whose Husbands' educational status of secondary [9][10][11][12] and college and above were 7.40 and 9.54 more likely took TT protective dose immunization as compared to never attended (AOR = 7.397, 95%CI: 1.873-29.211) (AOR = 9.539, 95%CI: 2.277-39.969) respectively. The odds of TT protective dose immunization were 3.98 times higher among mothers who stated that the provision of TT vaccine service was good" than their counterparts (AOR = 3.978, 95%CI 1.303-12.146).…”
Section: Factors Associated With Tetanus Toxoid Protective Dose Immunizationmentioning
confidence: 99%
“…9 A cross-sectional study conducted in Ibadan, Nigeria revealed that about 81.1% of mothers were taken at least two doses of TT vaccine. 10 Ethiopian demographic and health survey (EDHS 2016) report showed that the proportion of TT protective dose immunization was 49%. 11 A systematic review and Meta-analysis done on TT protective dose immunization in Ethiopia is also showed that about 52.6% of women were vaccinated during pregnancy at least twice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation